"The switch doesn't turn off": a mixed-methods exploratory study of cross-cultural education and practice in medical social work - Gallo, Nathan, author; Currin-McCulloch, Jennifer, advisor; MacPhee, David, committee member; Sagás, Ernesto, committee member (Colorado State University. Libraries, 2025)
The current version of cross-cultural social work education has left medical social workers inadequately prepared for the ever-changing face of the United States. In response, this mixed-methods exploratory study aimed to address gaps to practically understand how cross-cultural education applies to medical social workers' practice as they support the seriously ill and dying. Topics focused on social workers' (1) preferred cross-cultural educational framework, (2) culture-related practice barriers, and (3) range of practice interventions. Participants (n = 4) completed an online survey capturing sociodemographic data, frequency of exposure to cross-cultural care, and influences on practice. Data analysis was limited to descriptive statistics due to the small sample size. Notably, zero social workers reported high agreement that their social work education provided adequate preparation for cross-cultural care. Survey data was subsequently integrated through an instrumental, within-case method to further understand the on-the-ground social work experience. Two interviews took place with a pediatric palliative care social worker (N = 1), analyzed through a reflexive thematic analysis (RTA) methodology. Four themes were crafted from her insights: don't stop learning and growing; cross-cultural care is a dance; cultural resources need to be strengthened; and policy limits quality cross-cultural care. Implications from the study include treating culture in social work education and practice as essential, rather than a consideration; developing and implementing a universal cultural assessment; and reforming institutional policy to be more culturally responsive. Further empirical study and debate is needed to sharpen the field's alternative cross-cultural frameworks, applied to the people who need it most: the patients and families we work with every day.
The switch doesn't turn off: a mixed-methods exploratory study of cross-cultural education and practice in medical social work
Keywords: cross-cultural practice; end of life; seriously ill and dying; cultural responsiveness; cross-cultural education; medical social work